"A Stepping Stone That Just Pushed Me Further Into Wanting to Go to University" : Student Perspectives on 'What Works' for Effective Outreach Strategies for Indigenous Students. - Barney, Katelyn; Williams, Hayley (Student Success v.12 n.2 p.8-17 https://doi.org/10.5204/ssj.1913, 2021)
In Australia, there are numerous outreach initiatives run by universities for Indigenous high school students that attempt to elevate aspirations of Indigenous students to go to university. The theoretical case for these initiatives is strong as much data exists surrounding the barriers Indigenous students face in entering university. However, the research and evidence base for these equity programs remains largely underdeveloped and limited (Bennett et al., 2015). Drawing on findings from interviews with Indigenous university students as part of a National Centre for Student Equity in Higher Education (NCSEHE) Equity Fellowship, this paper identifies what works and what areas to strengthen in Indigenous specific outreach programs. The paper concludes by discussing the development of strategies and resources to build the evidence base of effective outreach activities for Indigenous students. [Author abstract]